Effectiveness of GSDL Model on Attitudes Toward Mathematics in Basic School of Nepal - Pokhrel, Maheshwor; Sharma, Lekhnath; Poudel, Madhav Prasad; GC, Laxmi (Educational Journal, 2026)
This study aims to find effectiveness of a Guided Self-Directed Instructional Model on Students attitude toward learning mathematics. Guided by positivist philosophical, we had employed experimental research design with innovative guided self-directed instructional learning model designed by Pokhrel (2026) in mathematics class. This model thus employs specific instructional strategies in a structured, progressive set of stages to transform a teacher-dependent learner to self-directed learner. The GSDL model was implemented in two groups of grade eight student in basic schools one was public and the other was private consisted of 56 students. Effectiveness of the GSDL was using the Students’ attitudes toward mathematics scale. IBM SPSS Version 26 was used to analyze quantitative data. The result concludes that students in both school private and public had unfavorable attitude toward mathematics in pretest result but improved favorable attitude after GSDL intervention. There was significance difference of mean attitude toward mathematics between pre and post test result, showed that GSDL intervention had positive effect on student’s overall attitudes toward mathematic in both private and public school. Moreover, showed that GSDL model was equally effective in improving attitudes toward mathematics in both private and public school. It can be concluded that the structured stage base GSDL instructional model shifts the pedagogical approach from teacher-directed to student-directed learning in the given stages of learning for improving mathematic achievement.